2010
DOI: 10.1124/dmd.110.036996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Liver Enzymes Involved in the Biotransformation of Boceprevir, a Hepatitis C Virus Protease Inhibitor

Abstract: ABSTRACT:Boceprevir (SCH 503034), a protease inhibitor, is under clinical development for the treatment of human hepatitis C virus infections. In human liver microsomes, formation of oxidative metabolites after incubations with [ 14 C]boceprevir was catalyzed by CYP3A4 and CYP3A5. In addition, the highest turnover was observed in recombinant CYP3A4 and CYP3A5. After a single radiolabeled dose to human, boceprevir was subjected to two distinct pathways, namely cytochrome P450-mediated oxidation and ketone reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 18 publications
2
46
0
2
Order By: Relevance
“…As BOC has low passive permeability and is eliminated primarily via hepatic metabolism by CYP3A4/5 and aldoketoreductases (Ghosal et al, 2011), uptake transporters may play an important role in the hepatic elimination of BOC. Our studies indicated that uptake of BOC in human hepatocytes was saturable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As BOC has low passive permeability and is eliminated primarily via hepatic metabolism by CYP3A4/5 and aldoketoreductases (Ghosal et al, 2011), uptake transporters may play an important role in the hepatic elimination of BOC. Our studies indicated that uptake of BOC in human hepatocytes was saturable.…”
Section: Discussionmentioning
confidence: 99%
“…Biotransformation is a major elimination pathway for BOC across preclinical species and humans. BOC undergoes extensive metabolism involving both cytochrome P450 (P450) CYP3A4/ 5-mediated oxidation and ketoreduction by cytosolic aldo-keto reductases (AKR)1C2 and AKR1C3 (Ghosal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Boceprevir is a potent, orally administered ketoamide inhibitor targeting the active site of the hepatitis C virus nonstructural protein 3 (NS3) protease, approved for the treatment of genotype 1 chronic hepatitis C virus infection in adult patients with compensated liver disease (3)(4)(5)(6). Addition of boceprevir to a pegylated interferon (peginterferon)-ribavirin backbone is associated with significantly increased rates of sustained virologic response (SVR) (7,8).…”
mentioning
confidence: 99%
“…Addition of boceprevir to a pegylated interferon (peginterferon)-ribavirin backbone is associated with significantly increased rates of sustained virologic response (SVR) (7,8). It is metabolized by aldoketoreductase and CYP3A4 and is a direct competitive and time-dependent inhibitor of CYP3A4/5, with inhibition constants in the low micromolar range (6), thus having the potential for drug-drug interactions with agents that are metabolized via these common pathways (3,5). In vitro, boceprevir has been shown to inhibit the hepatic uptake transporter organic anion transporting polypeptide (OATP) 1B1 (50% inhibitory concentration [IC 50 ] of 18 M), but the clinical significance of this in vitro inhibition is unknown (6).…”
mentioning
confidence: 99%
“…The administration of such drugs in the context of HCV recurrence on the liver graft is one of the most important clinical challenges in the field of LT. One limitation is the potential for interaction with calcineurin inhibitors such as cyclosporine and tacrolimus (5). Two distinct pathways extensively metabolize boceprevir, the cytochrome P450 (CYP) (mainly CYP3A) and aldo-ketoreductase pathways (11). Boceprevir is a potent inhibitor of CYP3A4 based on the results of in vitro assessments and of drug-drug interaction studies performed with oral midazolam, with coadministration increasing more than 5-fold the midazolam exposure (17).…”
mentioning
confidence: 99%